2019
DOI: 10.5194/acp-2019-895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decadal changes in anthropogenic source contribution of PM<sub>2.5</sub> pollution and related health impacts in China, 1990–2015

Abstract: Abstract. Air quality in China has changed dramatically in response to rapid development of economy and policies. In this work, we investigate the changes of anthropogenic source contribution to ambient fine particulate matter (PM2.5) air pollution and related health impacts in China during 1990–2015 and elucidate the drivers behind the decadal transition. We estimate the contribution of five anthropogenic emitting sectors to ambient PM2.5 exposure and related premature mortality over China during 1990… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(52 reference statements)
0
3
1
Order By: Relevance
“…In comparison, the power sector (15%) is a smaller source, which is inconsistent with the findings reported in previous studies (Klimont et al, 2017). This occurs because pronounced SO2 emission abatements occurred in China from 2013-2017 due to the ultralow-emission retrofitting of coal-fired power (Liu et al, 2020). Transportation (40%), especially heavy-duty diesel vehicles (25%), predominantly contributes to NOx emissions, followed by industrial combustion and process (36%) and power plants (11%).…”
Section: Base Year Emission Inventorycontrasting
confidence: 78%
“…In comparison, the power sector (15%) is a smaller source, which is inconsistent with the findings reported in previous studies (Klimont et al, 2017). This occurs because pronounced SO2 emission abatements occurred in China from 2013-2017 due to the ultralow-emission retrofitting of coal-fired power (Liu et al, 2020). Transportation (40%), especially heavy-duty diesel vehicles (25%), predominantly contributes to NOx emissions, followed by industrial combustion and process (36%) and power plants (11%).…”
Section: Base Year Emission Inventorycontrasting
confidence: 78%
“…The uncertainties from the historical emission inventories are widely quantified in previous works (e.g. Zhang et al, 2009;Lei et al, 2011a;Lu et al, 2011;Li et al, 2017). These uncertainties may pass to our projection model and create new uncertainties in the emission reduction rates and future emission mitigation pathways, but there are few impacts on the emission estimates for the year 2050.…”
Section: Limitations and Uncertaintiesmentioning
confidence: 99%
“…The rapid development of China has led to severe air pollution due to the ever-increasing energy demand and lax environmental legislation over the past decades, and this exerts negative influences on human health, climate, agriculture, and ecosystems (Liu et al, 2019;Xue et al, 2019a;. In 2013, China implemented the Air Pollution Prevention and Control Action Plan (denoted the Action Plan) to fight against air pollution (China State Council, 2013), and a series of active clean air policies for various sectors were adopted in support of the Action Plan.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Liu et al (2020) and Xing et al (2015) showed that with the rapid development of the economy and urbanization, China has been suffered from severe air pollution in recent years. In 2013 and 2018, the Chinese government implemented a series of interventions and launched policies on air quality control.…”
Section: Introductionmentioning
confidence: 99%